Fabrication of hexagonal zinc oxide nanorods on seeded substrate via hydrothermal method - Maarof, Nurul Amiera Shahida (2022)
Zinc oxide (ZnO) has been studied due to have a direct wide bandgap (~3.7 eV), large exciton binding energy (~60 meV), non-toxic material. In this study, two step hydrothermal process was introduced to fabricate seed layer in a form of ZnO nanoparticles (ZnO-NPs) and ZnO nanorods (ZnO-NRs). The seed layer solution concentration is 0.3 M and consists of zinc acetate dihydrate (ZAD) and diethanolamine (DEA). Besides that, 5 layers of coated seed layer was deposited using spin coating method. Subsequently, the high quality of aligned hexagonal ZnO-NRs were fabricated using hydrothermal method which consists of an equimolar nutrient solution (0.05 M) synthesized using zinc nitrate hexahydrate (ZNH) and hexamethylenetetramine (HMTA). The hydrothermal reaction times were varied from 1 hour to 9 hours. The structural, morphological, topological, optical and electrical properties of the ZnO-NRs were studied using X-ray diffraction (XRD), Field-Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy (AFM), Ultraviolet-visible (UV-Vis) spectroscopy and four-point probe, respectively. Based on the research, the deposition of ZnO-NPs indicated a significant improvement in the well-developed and aligned hexagonal of ZnO-NRs. As a result, ZnO-NRs synthesized with 6 hours of hydrothermal reaction time had an average diameter of 185 nm and rod lengths of 2.04 μm. However, recorded the lowest value of resistivity (0.83 x10-3 Ω.cm) thus, exhibited the highest value of conductivity (12.11 x102 Ω.cm-1). As higher conductivity materials can transfer more electrons, thereby increasing the rate of electron-hole generation. This will lead to greater current flows. Therefore, ZnO-NRs can be widely implemented in electronic devices application such as ultraviolet sensor and thermoelectric application.